The Influence of Fintech Technology Usage (Equity Crowdfunding and Peer-to-Peer Lending) on Investment Funding Decisions and Their Implications for Market Risk (Value at Risk) in Digital Startups in Indonesia - Hanifan, Zakie; Novianty, Ina (Educational Researcher Journal, 2026)
Objective – This study aims to analyze the influence of the use of fintech technology, namely equity crowdfunding (ECF) and peer-to-peer lending (P2P), on investment funding decisions and their implications for market risk ( Value at Risk / VaR) in digital startups in Indonesia. Methods – The study employed a mixed methods approach with a predominantly quantitative design. The sample consisted of 178 Indonesian digital startups registered with the Ministry of Communication and Information Technology (Kominfo) and AFTECH, selected using purposive sampling . Primary data were collected through a Likert-scale questionnaire, while secondary data consisted of financial reports and fintech transactions for 12 months. VaR was calculated using the Historical Simulation method (CI 95%). Data analysis used PLS-SEM with SmartPLS 4.0, supplemented by semi-structured interviews for triangulation. Results – All five hypotheses were significantly accepted (p < 0.01). Equity crowdfunding (β=0.348) and P2P lending (β=0.427) positively influenced investment funding decisions, with P2P having a greater influence due to its liquidity speed and working capital flexibility. Investment funding decisions further positively influenced VaR (β=0.521). Startups using a combination of ECF and P2P had the highest VaR (8.15% of total assets), while those using ECF alone had the lowest (4.28%). These findings confirm a trade-off between funding accessibility through fintech and market risk stability. The study also extends pecking order theory in the context of digital startups and provides practical implications for startups, fintech platforms , and the Financial Services Authority (OJK) regulator